Improving gingival smile by means of guided bone regeneration principles - Carlos Eduardo de Almeida Ferreira; Roberto Carlos Bodart Brandão; Carolina Borges Martinelli; Túlio Bonna Pignaton
ABSTRACT Objective: This study evaluated the effectiveness of guided bone regeneration (GBR) carried out with xenogenic bone substitute (Bio-OssTM) and collagen resorbable membrane (Bio-GideTM) to improve gingival smile (GS) in patients with excessive vertical maxillary growth (EVMG). Methods: Twelve healthy women aged between 20 and 49 years old (mean age of 26 years), with 5 mm or more of gingival exposure during fully posed smile (FPS) due to EVMG, were included. Baseline digital photographs were taken with standardized head position at rest and FPS. In eight out of 12 cases, crown lengthening procedure was indicated and the initial incision was made 2 to 4 mm from the gingival margin. In four cases, with no indication for crown lengthening procedure, a sulcular incision was performed. GBR was performed in all cases, using micro screws and/or titanium mesh associated with Bio-OssTM and Bio-GideTM. After 10 days, sutures were removed. Recall appointments were scheduled at 1, 6, and 12 months when standardized photographs were again taken. ImageToolTM software was used to measure the gingival exposure (GE) during FPS from the standardized close-up smile photographs at baseline and 12 months. Results: GE mean at baseline was 275.44 mm2. After 12 months, patients who undergone exclusively GBR procedure, presented GE reduction of 40.7%, ∆ = 112.01 mm2 (statistically significant, p = 0.12), and patients who had crown lengthening associated with the graft had a reduction of 60%, ∆ = 167.01 mm2. Conclusion: Our results using GBR to improve GS in cases of EVMG showed an exceptionally high patient acceptance and satisfaction. One-year follow-up confirmed stable results.